2010
DOI: 10.7547/1000401
|View full text |Cite
|
Sign up to set email alerts
|

A Stepwise Approach for Surgical Management of Diabetic Foot Infections

Abstract: Diabetic foot disease frequently leads to substantial long-term complications, imposing a huge socioeconomic burden on available resources and health-care systems. Peripheral neuropathy, repetitive trauma, and peripheral vascular disease are common underlying pathways that lead to skin breakdown, often setting the stage for limb-threatening infection. Individuals with diabetes presenting with foot infection warrant optimal surgical management to affect limb salvage and prevent amputation; aggressive short-term… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
10
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(10 citation statements)
references
References 20 publications
0
10
0
Order By: Relevance
“…64 In particular, patients with a foot infection are at high risk for limb loss and should be treated as a medical emergency. The 1-year major amputation rate for such patients has been reported to be as high as 44%, 65 and delay in treatment can lead to rapid tissue destruction and lifethreatening sepsis 66 In those patients in whom the risk-benefit ratio of revascularization is unclear, it should be taken into account that some severely ischaemic ulcers heal without revascularization-two observational studies demonstrated healing rates of around 50% (with or without minor amputations) in patients unsuitable (either because they were deemed too frail or where revascularization was not technically possible) for revascularization. 10 There are several other techniques that have been investigated for patients with diabetes, PAD, and ulceration in whom there are no options for revascularization.…”
Section: Rationalementioning
confidence: 99%
“…64 In particular, patients with a foot infection are at high risk for limb loss and should be treated as a medical emergency. The 1-year major amputation rate for such patients has been reported to be as high as 44%, 65 and delay in treatment can lead to rapid tissue destruction and lifethreatening sepsis 66 In those patients in whom the risk-benefit ratio of revascularization is unclear, it should be taken into account that some severely ischaemic ulcers heal without revascularization-two observational studies demonstrated healing rates of around 50% (with or without minor amputations) in patients unsuitable (either because they were deemed too frail or where revascularization was not technically possible) for revascularization. 10 There are several other techniques that have been investigated for patients with diabetes, PAD, and ulceration in whom there are no options for revascularization.…”
Section: Rationalementioning
confidence: 99%
“…DFI is the leading cause of non-traumatic lower limb amputations. [4][5][6][7] The main aim was to study the DFI which is responsible for increased morbidity, amputations and even mortality in diabetic patients. [8][9][10] Diabetic foot infections were more common (33.33%) in age group of 45-54 years whereas P.C Leung reported 75% infections occurred above the age of 50 years.…”
Section: Discussionmentioning
confidence: 99%
“…A limb preservation team must be able to perform bedside and intraoperative incision and debridement to decompress limb-threatening abscesses and debride nonviable tissue. Surgeons involved in this care should have knowledge and interest in this aspect of limb preservation (25). If insufficient blood flow to the extremities impairs delivery of antibiotics or oxygen, revascularization should be done as soon as the major infection has been adequately addressed.…”
Section: Surgical Management Of Infectionsmentioning
confidence: 99%